First genotype‐phenotype study reveals HLA‐DQβ1 insertion heterogeneity in high‐resolution manometry achalasia subtypes. Issue 1 (1st February 2019) - Vackova, Zuzana; Niebisch, Stefan; Triantafyllou, Tania; Becker, Jessica; Hess, Timo; Kreuser, Nicole; Kanoni, Stavroula; Deloukas, Panos; Schüller, Vitalia; Heinrichs, Sophie KM; Thieme, René; Nöthen, Markus M; et al.
Abstract : Background: Achalasia is a primary oesophageal motility disorder. Although aetiology remains mainly unknown, a genetic risk variant, rs28688207 in HLA‐DQB1, showed strong achalasia association suggesting involvement of immune‐mediated processes in the pathogenesis. High‐resolution manometry recognises three types of achalasia. The aim of our study was to perform the first genotype‐phenotype analysis investigating the frequency of rs28688207 across the high‐resolution manometry subtypes. Methods: This was a cross‐sectional retrospective study. Achalasia patients from tertiary centres in the Czech Republic ( n = 163), Germany ( n = 114), Greece ( n = 70) and controls were enrolled. All subjects were genotyped for the rs28688207 insertion. The Kruskal–Wallis test was used for the genotype‐phenotype analysis. Results: A total of 347 achalasia patients (type I – 89, II – 210, III – 48) were included. The overall frequency of the rs28688207 was 10.3%. The distribution of the insertion was significantly different across the high‐resolution manometry subtypes ( p = 0.038), being most prevalent in type I (14.6%), followed by type II (9.5%) and III (6.3%). Conclusion: The frequency of the HLA‐DQB1 insertion differs among high‐resolution manometry achalasia subtypes. The insertion is most prevalent in type I, suggesting that immune‐mediated mechanisms triggered by the insertion may play a more prominent role in the pathogenesis of this subtype.